Boosting Alkaline Hydrogen Evolution Reaction via an Unexpected Dynamic Evolution of Molybdenum and Selenium on MoSe2 Electrode. Issue 47 (26th October 2022) - Zhou, Lihai; Yang, Chunming; Zhu, Wangchuan; Li, Ran; Pang, Xiangxiang; Zhen, Yanzhong; Wang, Chuantao; Gao, Loujun; Fu, Feng; Gao, Ziwei; Liang, Yucang
Abstract: Transition metal chalcogenides are a promising and extremely pivotal class of electrocatalysts with potential applications in alkaline hydrogen evolution reaction (HER), especially, molybdenum diselenide. Although the exposed edge sites are generally considered to be the active sites of MoSe2 for HER, an intrinsic behavior (surface species evolution, structure/morphology conversion, stability) of MoSe2 electrode itself was not unveiled. Herein, the origin of MoSe2 ‐electrocatalyzed HER activity monitored by the quasi‐operando XPS and in situ Raman spectroscopy is presented. The findings clearly show dynamic evolution of both Mo and Se species on MoSe2 electrode surface for promoting HER activity and maintaining long‐term catalytic stability and reveal an electro‐oxidative dissolution and re‐adsorption mechanism. Theoretical calculations also corroborate these results. As expected, the addition of single or mixed MoO4 2− and SeO3 2− to the electrolyte of nickel foam directly verifies the critical role of surface‐adsorbed Mo and Se species for boosting HER activity and stability. Additionally, the oxidative dissolution of Se on Ni x Se y electrode surface during HER is also observed, revealing the universality of oxidative dissolution of Se in transition metal selenides. This study provides a unique insight into the species evolution and surface structure transformation mechanism and activity improved origin of materials during the electroreduction process. Abstract : MoSe2 is an efficient and pivotal electrocatalyst in alkaline water splitting. Herein, this study presents how MoSe2 electro‐catalyzes the hydrogen evolution reaction (HER) and what species promote HER activity and make the MoSe2 electrode maintain a long‐term stability in alkaline environment. Based on experimental results, a dynamic equilibrium process of oxidative dissolution–adsorption of Mo and Se in MoSe2 is suggested.